Persistent opioid use in cataract surgery pain management and the role of nonopioid alternatives. Issue 6 (12th June 2022) - Davidson, Richard S.; Donaldson, Kendall; Jeffries, Maggie; Khandelwal, Sumitra; Raizman, Michael; Rodriguez Torres, Yasaira; Kim, Terry
Abstract : Cataract surgery pain management in light of the opioid crisis and how ophthalmologists can help make a positive impact with the use of non-opioid options is discussed. Abstract : Cataracts are a leading cause of preventable blindness globally. Although care varies between developing and industrialized countries, surgery is the single effective approach to treating cataracts. From the earliest documented primitive cataract removals to today's advanced techniques, cataract surgery has evolved dramatically. As surgical techniques have developed, so have approaches to surgical pain management. With current cataract surgical procedures and advanced technology, anesthesia and intraoperative pain management have shifted to topical/intracameral anesthetics, with or without low-dose systemic analgesia and anxiolysis. Despite this, pain and discomfort persist in some patients and are underappreciated in modern cataract surgery. Although pain management has progressed, opioids remain a mainstay intraoperatively and, to a lesser extent, postoperatively. This article discusses the evolution of pain management in cataract surgery, particularly the use of opioids and the associated risks as well as how ophthalmology can have a positive impact on the opioid crisis.